2017
DOI: 10.1124/dmd.117.075192
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Maternal-Fetal Physiologically Based Pharmacokinetic Model I: Insights into Factors that Determine Fetal Drug Exposure through Simulations and Sensitivity Analyses

Abstract: Determining fetal drug exposure (except at the time of birth) is not possible for both logistical and ethical reasons. Therefore, we developed a novel maternal-fetal physiologically based pharmacokinetic (m-f-PBPK) model to predict fetal exposure to drugs and populated this model with gestational age-dependent changes in maternal-fetal physiology. Then, we used this m-f-PBPK to: 1) perform a series of sensitivity analyses to quantitatively demonstrate the impact of fetoplacental metabolism and placental transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
115
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(123 citation statements)
references
References 113 publications
(79 reference statements)
0
115
0
Order By: Relevance
“…Another approach was presented by Zhang et al for compounds crossing the placenta exclusively via passive diffusion . In this case, the fetal‐to‐maternal partition ratio was assumed to equal 1.0.…”
Section: Models For Placental Drug Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach was presented by Zhang et al for compounds crossing the placenta exclusively via passive diffusion . In this case, the fetal‐to‐maternal partition ratio was assumed to equal 1.0.…”
Section: Models For Placental Drug Transfermentioning
confidence: 99%
“…Apart from the explicit integration of placental transporters, these models may also benefit from finer representation of fetal physiology. Recently, several repositories have been published that review physiological changes in the fetus, such as organ growth, change in blood flow rates, tissue composition, and drug‐binding protein concentrations . In addition, drug transfer may also be influenced by the pH difference between the fetal and maternal blood.…”
Section: Models For Placental Drug Transfermentioning
confidence: 99%
“…At that time, different PBPK models for pregnant women were developed in MatLab or as part of Simcyp, GastroPlus, and also in the Open Systems Pharmacology (OSP) software suite which includes the software programs PK‐Sim and MoBi (https://github.com/Open-Systems-Pharmacology/Pregnancy-Models). Some of these models were subsequently used as a basis for further model refinement and/or incorporation of information on system‐specific parameters that were not part of the original model, such as changes in the activity of specific CYP enzymes . Furthermore, a variety of semimechanistic or minimal PBPK models for pregnant women can also be found in the literature .…”
Section: History and Recent Progress Of Pregnancy Pbpk Modelsmentioning
confidence: 99%
“…described such a feto‐pregnancy‐PBPK model in which a placenta, amniotic fluid compartment, and fetal organs that are relevant to drug disposition were added, the model also took into account typical characteristics of the fetal circulation. Gestational age‐dependent changes in fetal, placental, and maternal physiological parameters during the second half of pregnancy were described using empirically derived polynomial equations . Using the model, the authors elegantly demonstrated that cord to maternal plasma ratios, even at distribution equilibrium, do not indicate fetal drug exposure relative to that in the mother, which is due to the time‐dependent distributional kinetics of drugs across the placenta.…”
Section: Modeling Placental Transfer and Fetal Exposure Of Drugsmentioning
confidence: 99%
“…In addition, they used sensitivity analysis to assess the possible impact of gestational age‐dependent changes in placental metabolism and transport processes on placental transfer. To verify performance of the model for predicting the placental passage of only passively diffusing drugs, the authors populated the model using midazolam as a calibrator drug, and subsequently verified the model by adequately predicting the fetal exposure of two other passively diffusing drugs, theophylline and zidovudine . For antiretroviral agents, similar approaches for incorporating placental transfer and drug disposition in lumped fetal compartments have been described by De Sousa Mendes et al .…”
Section: Modeling Placental Transfer and Fetal Exposure Of Drugsmentioning
confidence: 99%